The Renal Manifestations of SARS-CoV-2: A Guide for Family Physicians - Austin P. Morrissey; Nagla Elzinad; Chris El Hayek; Saran Lotfollahzadeh; Vipul C. Chitalia (International Journal of Translational Medicine, 2023)
COVID-19 is a devastating systemic disease characterized by multisystem involvement driven by exuberant hyperinflammatory and dysregulations in coagulation. In COVID-19 patients, renal failure contributes to morbidity and mortality, and its early detection and timely management are critical to minimize such untoward and irreversible complications. In the healthcare system, family physicians constitute the first node in the management of patients, yet there is a dearth of reports and guidelines focusing on them for specific organ affection. This review provides an overview of recent studies examining the renal manifestations following SARS-CoV-2 infection. We focus on the tell-tale signs and laboratory findings of renal affection in the pediatric and adult populations with COVID-19, specifically for family practitioners to assist in their appropriate triage. Among different manifestations, urinary abnormalities and a modest increase in creatinine are the early indicators of renal affection in COVID-19 patients. Although renal transplant patients are conventionally managed by specialized teams, they may present to family physicians during a pandemic. This review provides a framework for family physicians to promptly detect early indicators of renal involvement in patients infected with SARS-CoV-2, including providing triage guidance for kidney transplant recipients.